1982
DOI: 10.1093/carcin/3.9.1063
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of pancreatic carcinogenesis. VI. Early changes in hamster acinar cells induced by N-nitroso-bis(2-hydroxy-propyl)amine

Abstract: Male Syrian golden hamsters were given weekly s.c. injections of 250 mg/kg body weight of N-nitroso-bis(2-hydroxypropyl)amine (BHP) for up to 15 weeks. Electron microscope studies were carried out on early changes in the exocrine pancreas of these hamsters for 2 weeks to 15 weeks. The majority of observed alterations occurred in the acinar cells and included the appearance of "dark" and "light" cells, the former showing nuclear shrinkage and irregularity but maintaining a normal rough endoplasmic reticulum (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Indeed, BHP treatment resulted in very little acinar necrosis, although mitotic cells were observed. However, these rough ER changes are not specific either to BHP or to carcinogens (84).…”
Section: Changes In Acinar Cellsmentioning
confidence: 82%
See 2 more Smart Citations
“…Indeed, BHP treatment resulted in very little acinar necrosis, although mitotic cells were observed. However, these rough ER changes are not specific either to BHP or to carcinogens (84).…”
Section: Changes In Acinar Cellsmentioning
confidence: 82%
“…Conventional histology revealed little change in the hamster pancreas until after 9 weeks of BHP treatment, when an apparent increase in centroacinar or ductulartype cells becanme evident (79,84). A quantitative study (Moore, unpublished observations) showed, over the first 15 weeks of treatment, a progressive increase in groups containing three or more centroacinar cells and a decline in single cells.…”
Section: Changes In Acinar Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…There are no other pancreatic cells with this ability, and there is evidence that the ductular cells and centroacinar cells are the most responsive units of the ductal system (2,3,14), based on their enormous potential to display a wide spectrum of phenotypic expression, including various forms of metaplastic change (Figs. [3][4][5][6][7][8]. Formation of glycogen-containing cells ( Fig.…”
Section: Histogenesis Of Exocrine Pancreatic Cancermentioning
confidence: 99%
“…There are three main points of view with regard to this element of the model. One group of investigators believes pancreatic lesions [at least those induced by Ai N-nitrosobis(2-hydroxypropyl)amine or BHP] derive from acinar cells that undergo ductlike dedifferentiation during carcinogenesis (4,5). Another group has the ,, distinct view that all induced lesions in hamsters derive i from ductal and ductular cells (2,3,6,7).…”
mentioning
confidence: 99%